RADICALS OF SUBMODULES IN MODULES - Yesilot, Gursel (AKADEMIAI KIADO RT, 2010)
The radical rad N of a submodule N of a module M is defined as the intersection of all prime submodules containing N. In this paper, we show that if the ideals (N : M) and (L : M) are comaximal then the equality rad (N boolean AND L) = rad N boolean AND rad L holds. We also discuss some properties of finitely generated R-modules.
Keywords: Radical submodule; Mathematics